Union of Civilian Personnel in Defence Establishments 1881-1950 - Lundkvist, Sven; Andrae, Carl-Göran; University of Gothenburg (Uppsala University, 1993)
To enable regional statistical analyses, the Swedish Social Science Data Service (SSD) carried out a radical reorganization of the source material from the Popular Movement Archive 1881–1950 (https://doi.org/10.5878/002531) in the early 1990s. The original hierarchically structured county files were remade into a series of rectangular files in accordance with a division of the country which mainly coincides with the pre-1952 municipal division of towns and country municipalities. To achieve comparability with other data materials, the division used by Sten Berglund in Swedish electoral data 1911-1944 (https://doi.org/10.5878/000873) was chosen.

The Popular Movement Archive includes information on four denominations, six temperance movements, 59 trade unions and one political party, a total of 70 popular movements. For each of these, a special rectangular file has been created, covering the entire country, and comprising 2,576 units, the same number as in Swedish electoral data 1911-1944.

For further information see the document: SSD:s omorganisation av Folkrörelsearkivet 1881-1950

För att möjliggöra regionalstatistiska analyser gjorde man vid Svensk Samhällsvetenskaplig Datatjänst (SSD) i början av 1990-talet en radikal omorganisering av källmaterialet från Folkrörelsearkivet 1881–1950 https://doi.org/10.5878/002531. De ursprungliga hierarkiskt uppbyggda länsfilerna omskapades till en serie rektangulära filer i enlighet med en indelning av landet som huvudsakligen sammanfaller med kommunindelningen före 1952 med städer och landskommuner. För att nå jämförbarhet med andra datamaterial valdes den indelning som utnyttjades av Sten Berglund i Svenska valdata 1911-1944, https://doi.org/10.5878/000873.

Folkrörelsearkivet omfattar uppgifter om fyra samfund, sex nykterhetsrörelser, 59 fackförbund och ett politiskt parti, sammanlagt 70 folkrörelser. För var och en av dessa har en särskild rektangulär fil skapats, täckande hela landet och omfattande 2576 enheter, samma antal som i Svenska valdata 1911-1944.

För ytterligare information se dokumentet: SSD:s omorganisation av Folkrörelsearkivet 1881-1950
Försvarsverkens civila personals förbund 1881-1950
Keywords: membership; medlemskap; labour movement; arbetarrörelse; trade union membership; medlemskap i fackförening; trade unions; fackföreningar; popular movement; folkrörelse; HISTORY; HISTORIA; Government, political systems and organisations; Regering, politiska system och organisationer; Political Science; Statsvetenskap; History; Historia